(untitled) (BIRDEM Medical Journal, 2021)
Background: Systemic lupus erythematosus (SLE) is a chronic, multisystem disorder that can affect any organ of the body. Approximately 80 percent of patients develop skin disease at some point in their disease course. The association with SLE varies among the subtypes of cutaneous lupus erythematosus (LE). Better understanding of cutaneous manifestations can help in more effective management. This study aimed to evaluate the pattern of cutaneous manifestations of SLE and to find out association with organ involvement. Methods: This cross-sectional observational study was conducted in the Green Life Medical College Hospital from January 2019 to December 2020. Sixty four lupus patients who fulfilled the SLICC 2012 classification criteria and having new onset or preexisting skin complaints were enrolled. Mixed connective tissue disease and other overlap syndromes were excluded. All patients were evaluated by a dermatologist and diagnosis was done as per modified Gilliam Classification criteria. Results: Out of 64 patients, 56 were female and 8 were male. Female and male ratio was 7:1. Mean age was 28.4±9.6 years. Among the cutaneous manifestations, LE specific was 38 (59.4%), LE non-specific was 41 (64.1%). Among LE specific, 66% were acute (ACLE), 42% were sub-acute (SCLE) and 37% patients were chronic (CCLE). Among ACLE, 72% had malar rash and 84% had photosensitivity. Among SCLE, most common was papulosqumous (68%). DLE (86%) was the most common CCLE. Among LE non-specific, 85% had non-scarring alopecia, 52% had vascular abnormalities. Most common organ involvement was musculoskeletal (84%), then renal (56%). DLE had negative association with renal involvement [OR (-0.04)]. No other cutaneous manifestations showed any significant association with any other organ involvement. Conclusion: Cutaneous manifestations are important feature in SLE. LE non-specific was more common than LE specific manifestations in this study. Better understanding can help in efficient diagnosis and management. BIRDEM Med J 2022; 12(1): 57-61